High Frequency Jet Ventilation in Respiratory Failure Secondary to Respiratory Syncytial Virus Infection: A Case Series - Valentine, Kevin M.; Sarnaik, Ajit A.; Sandhu, Hitesh S.; Sarnaik, Ashok P. (Frontiers in Pediatrics, 2016)
Objective To describe the utility of high frequency jet ventilation (HFJV) as a rescue therapy in patients with respiratory failure secondary to respiratory syncytial virus (RSV) that was refractory to conventional mechanical ventilation (CMV). Design Descriptive study by retrospective review. Setting Pediatric intensive care unit at a tertiary care children’s hospital. Patients Infants on mechanical ventilation for respiratory failure due to RSV. Interventions Use of HFJV. Main Results Eleven patients were placed on HFJV. There was sustained improvement in ventilation on HFJV with a mean decrease in PCO2 of 9 mmHg at 24 h and 11 mmHg at 72 h. There were no significant changes in oxygenation by oxygenation index. No patients required extracorporeal support or suffered pneumothorax, pneumomediastinum, or subcutaneous emphysema. Ten out of 11 (91%) patients survived to discharge from the hospital. Conclusion High frequency jet ventilation may represent an alternative therapy for RSV-induced respiratory failure that is refractory to CMV.